HOW TO MAKE ECOPRINT ON MASK IN THE CONTEXT OF COVID-19 PREVENTION BASED ON ECO GREEN at HIRZU MILLATI ISLAMIC BOARDING SCHOOL, SINGOCANDI KUDUS - Rohmatun Nafi'ah; Arina Hafadhotul Husna (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STIKES Cendekia Utama Kudus, 2021)
Along with the increasing number of Covid-19 cases in Kudus Regency, which greatly affects people's lifestyles. For this reason, STIKES Cendekia Utama Kudus performs Community Service. This community service aims to provide soft skill training in making Ecoprints on Masks as an effort to prevent Covid-19 based on Eco Green, because wearing masks is one of the efforts in preventing Covid-19. In addition, by providing English language training on